2016
DOI: 10.1002/app.44166
|View full text |Cite
|
Sign up to set email alerts
|

Retarding hydrolytic degradation of polylactic acid: Effect of induced crystallinity and graphene addition

Abstract: The combination of elevated temperature and humidity leads to rapid degradation of polylactic acid (PLA) because of hydrolysis. Consequently, PLA, which is a bio-derived and biodegradable polymer, is not currently used for durable applications since properties cannot always be maintained over time. In this work, the ability of polymer crystals to reduce the rate of degradation during accelerated aging tests was studied. Also examined was the influence of addition of 2 wt % graphene nanoplatelets to act as mois… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…Without degradation water barrier and reduced the mobility of the amorphous phase and hindering water diffusion into the sample. Finniss et al [26] observed that the incorporation of 2 wt% of graphene nanoplatelets in PLA acted as water transport barriers, retarding hydrolytic degradation of PLA. Peponi et al [27] observed that PLA/PCL blend reinforced with 0.5 wt%, 1 wt% or 3 wt% hydroxyapatite presented lower disintegration rates than the unmodified blend under compost conditions.…”
Section: Water Uptake and Weight Loss Measurementsmentioning
confidence: 99%
“…Without degradation water barrier and reduced the mobility of the amorphous phase and hindering water diffusion into the sample. Finniss et al [26] observed that the incorporation of 2 wt% of graphene nanoplatelets in PLA acted as water transport barriers, retarding hydrolytic degradation of PLA. Peponi et al [27] observed that PLA/PCL blend reinforced with 0.5 wt%, 1 wt% or 3 wt% hydroxyapatite presented lower disintegration rates than the unmodified blend under compost conditions.…”
Section: Water Uptake and Weight Loss Measurementsmentioning
confidence: 99%
“…This is controlled by the rate constant, absorbed water, diffusion coefficient of chain fragments, and solubility of degradation products [4]. Many authors have studied hydrolytic degradation of PLA [28][29][30]. However, few studies have been conducted to study hydrolytic degradation of PBAT and PLA/PBAT blends with CEO.…”
Section: Introductionmentioning
confidence: 99%
“…Similar behavior was observed by Zhao et al [ 19 ], who developed nanocomposites of PLLA with multiwalled carbon nanotubes (MWNTs). Nevertheless, the literature also provides studies showing that the incorporation of graphene nanoplatelets into the polymer matrix produced the opposite effect, i.e., a reduction of the biodegradation rate of the material, due to the hydrophobic constitution of graphene [ 20 , 21 ]. Recently, Murray et al [ 21 ] reported the enzymatic degradation of PCL/rGO mixtures and composites.…”
Section: Introductionmentioning
confidence: 99%